Switched - Hocking, Amanda (New York : St. Martin's Griffin, 2012)
When Wendy Everly was six years old her mother was convinced she was a monster and tried to kill her, and eleven years later Wendy learns that her mother was right and that she is actually a changeling troll, who, at the age of seventeen, must be returned to her rightful home.
Includes bonus short story: The Vittra attacks (A Trylle story).
Keywords: Trolls -- Fiction; Changelings -- Fiction; Supernatural -- Fiction